UNLOCKING WORKFORCE EXCELLENCE: THE POWER OF LEADERSHIP, SKILLS, AND SATISFACTION - Dwi Monica Novianty; Muzakki Muzakki (Kesatuan Press, 2026)
Public sector organizations in Indonesia face persistent challenges related to low employee performance and job satisfaction, often driven by bureaucratic rigidity, lack of leadership innovation, and limited alignment between job competence and role demands. These issues undermine the quality of public service delivery and institutional effectiveness. Addressing this phenomenon, the present study investigates the influence of transformational leadership and job competence on job satisfaction and employee performance. Employing a quantitative approach, data were collected from 327 civil servants working in various local government agencies in Sumenep Regency. The relationships among variables were analyzed using Structural Equation Modeling (SEM). The results indicate that transformational leadership significantly enhances both job satisfaction and employee performance. Likewise, job competence emerges as a strong predictor of positive employee outcomes, indicating that competent employees are more engaged and productive. Furthermore, job satisfaction serves as a significant mediator in the relationship between leadership, competence, and performance. These findings are underpinned by Social Exchange Theory (SET), which highlights the role of reciprocal trust and supportive leadership in shaping positive work behaviors.